In Vitro Bioactivity Study of RGD-Coated Titanium Alloy Prothesis for Revision Total Hip Arthroplasty. (14th July 2016) - Man, Zhentao; Sha, Dan; Sun, Shui; Li, Tao; Li, Bin; Yang, Guang; Zhang, Laibo; Wu, Changshun; Jiang, Peng; Han, Xiaojuan; Li, Wei
Abstract : Total hip arthroplasty (THA) is a common procedure for the treatment of end-stage hip joint disease, and the demand for revision THA will double by 2026. Ti6Al4V (Titanium, 6% Aluminum, and 4% Vanadium) is a kind of alloy commonly used to make hip prothesis. To promote the osseointegration between the prothesis and host bone is very important for the revision THA. The peptide Arg-Gly-Asp (RGD) could increase cell attachment and has been used in the vascular tissue engineering. In this study, we combined the RGD with Ti6Al4V alloy using the covalent cross-linking method to fabricate the functional Ti6Al4V alloy (FTA). The distribution of RGD oligopeptide on the FTA was even and homogeneous. The FTA scaffolds could promote mouse osteoblasts adhesion and spreading. Furthermore, the result of RT-qPCR indicated that the FTA scaffolds were more beneficial to osteogenesis, which may be due to the improvement of osteoblast adhesion by the RGD oligopeptide coated on FTA. Overall, the FTA scaffolds developed herein pave the road for designing and building more efficient prothesis for osseointegration between the host bone and prothesis in revision THA.